Konsumsi BBM Perikanan Tangkap Tuna Cakalang Tongkol dengan Pancing Ulur di Pelabuhan Perikanan Pantai Pondokdadap - Jauza Zahira Rachman; Vita Rumanti Kurniawati; Tri Nanda Citra Bangun (JURNAL PERIKANAN DAN KELAUTAN, 2024)
Pondokdadap Coastal Fisheries Port (PPP) produces tuna, skipjack, and tuna (TCT) capture fisheries. TCT catches in 2021 reached 1,385,883 tons. The high TCT catch is also influenced by the large number of fishing fleets, which can affect the fuel consumed. This research aims to calculate fuel consumption for TCT catches at PPP Pondokdadap using a fleet of hand-line fishing vessels. The research methods used were interviews and literature studies. The sample selection used accidental sampling and purposive sampling techniques. The number of samples used was 32 ships measuring 9-28 GT. Based on the research results, the highest TCT catch in 2022 was 6,299 tons. The total fuel consumption is 15,126 kg/year and is used by ships measuring 21-24 GT. The average fuel consumption value is IDR 60,361,897.00 with an average fish production of IDR. 465,812,241. Meanwhile, the average value of Fuel Use Intensity of BBM per 1kg of fish is 0.66 kg and the average FUI value of income obtained is 137.55. The cost of purchasing fuel tends to be lower than the cost of income, so it can be concluded that fishermen do not experience losses.